Pandangan Abdurrahman Wahid tentang Relasi Islam dan Negara: Pendekatan Sosio-Kultural - Rochmat, Saefur (Millah: Journal of Religious Studies, 2011)
Abdurrahman Wahid introduces a socio-cultural approach to deal with the issue of the relationship between Islam and state. The approach is a kind of modification to the Fiqh approach advocated by Nahdhatul Ulama (NU) to suit it to the development of modern sciences as well as to understand the latter based on Islamic cosmology. According to him, Islamic identity is Islamic cosmology which views the spirit and the material intermingling in the worldly life. Accordingly Muslim should respond to the issues of modernity based on this Islamic tradition with the hope to direct the modernity discourses. By so doing it will help to mediate the conflict of ideologies based on its belief that “the normative” intermingles with “the particular” and as consequences there is no absolute truth prevailing in this worldly life.